Panel data econometrics - Badi H Baltagi (Contributions to economic analysis ;, 2006)
Panel data econometrics has evolved rapidly over the last decade. Dynamic panel data estimation, non-linear panel data methods and the phenomenal growth in non-stationary panel data econometrics makes this an exciting area of research in econometrics. The 11th international conference on panel data held at Texas A&M University, College Station, Texas, June 2004, witnessed about 150 participants and 100 papers on panel data. This volume includes some of the papers presented at that conference and other solicited papers that made it through the refereeing process. Contributions to Economic Analysis was established in 1952. The series purpose is to stimulate the international exchange of scientific information. The series includes books from all areas of macroeconomics and microeconomics.